Dampak Latihan Pec Crawl Terhadap Peningkatan Daya Tahan Otot Perut dan Core - Pratama, Agung Cahya; Erlina, Terra; Sugiawardana, Ruli; Rohendi, Andang; Kurniawan, Asep Ridwan (Universitas Galuh, 2025)
This study aims to determine the effect of pec crawl exercise on increasing abdominal and core muscle endurance. The research method used is pre-experimental design. The research location is SMP Negeri 1 Bantarkalong, Tasikmalaya Regency. The sampling technique is total sampling. The test instrument used is core muscle strength and stability test. Based on data analysis using SPSS series 26, the results of this study indicate that,